Gompertz model in COVID-19 spreading simulation. (January 2022) - Pelinovsky, E.; Kokoulina, M.; Epifanova, A.; Kurkin, A.; Kurkina, O.; Tang, M.; Macau, E.; Kirillin, M.
Highlights: The classical logistic and Gompertz models are used to interpret the first wave of COVID-19 pandemic in 23 countries. The models describe properly the growth in the number of confirmed cases with time. The Gompertz model demonstrates better fit of official statistics data compared to the classical logistic equation in all considered countries except Japan. Employment of the Gompertz model with delay did not reveal any effect of the delay time in providing better fit of the official statistics. Abstract: The paper reports on application of the Gompertz model to describe the growth dynamics of COVID-19 cases during the first wave of the pandemic in different countries. Modeling has been performed for 23 countries: Australia, Austria, Belgium, Brazil, Great Britain, Germany, Denmark, Ireland, Spain, Italy, Canada, China, the Netherlands, Norway, Serbia, Turkey, France, Czech Republic, Switzerland, South Korea, USA, Mexico, and Japan. The model parameters are determined by regression analysis based on official World Health Organization data available for these countries. The comparison of the predictions given by the Gompertz model and the simple logistic model (i.e., Verhulst model) is performed allowing to conclude on the higher accuracy of the Gompertz model.